2013
DOI: 10.1007/s10856-013-4936-z
|View full text |Cite
|
Sign up to set email alerts
|

Wear testing and particle characterisation of sequentially crosslinked polyethylene acetabular liners using different femoral head sizes

Abstract: Larger femoral heads lead to a decreased risk of total hip dislocation and an improved range of motion. However, the larger diameter is associated with increased wear rates. The low wear rates of crosslinked polyethylene opens up the possibility of using larger heads. The aim of this experimental study was to evaluate the wear of conventional non-crosslinked versus sequentially crosslinked polyethylene liners in combination with different ceramic head sizes (28, 36, 44 mm). Wear testing was performed in a hip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 50 publications
4
32
0
4
Order By: Relevance
“…In comparison to previous in vitro studies, the results showed that wear rates of both surface modifications were at least three-fold lower than these of traditional 36 mm CoCr-on-cross-linked polyethylene bearings [24][25][26][27]. Furthermore, the polyethylene wear could be reduced to the level of alumina ceramic heads [19,26].…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…In comparison to previous in vitro studies, the results showed that wear rates of both surface modifications were at least three-fold lower than these of traditional 36 mm CoCr-on-cross-linked polyethylene bearings [24][25][26][27]. Furthermore, the polyethylene wear could be reduced to the level of alumina ceramic heads [19,26].…”
Section: Discussionmentioning
confidence: 49%
“…These ceramic heads were tested as part of a previous wear study [19] which used the same loading scenario. Within the present study, contact angle measurements have been made at these ceramic heads.…”
Section: Test Specimensmentioning
confidence: 99%
See 2 more Smart Citations
“…The linear restraint system is characterized and discussed afterwards (see Table 4 and discussion). [64][65][66][67] wear testing of established artificial joints like the hip or the knee. Therefore, a comparably relevant wear volume is also generated for TAR.…”
Section: Clinical Relevancementioning
confidence: 99%